Pengaruh Terpaan Iklan Televisi dan Kualitas Website terhadap Keputusan Pembelian di Situs Belanja Online Bukalapak - Alifa Ardini Sekarpramudita; Yanuar Luqman (Interaksi Online, 2020)
The purpose of this study was to determine the effect of exposure to television advertising and website quality on purchasing decisions on Bukalapak online shopping sites. This study uses the theory of advertising exposure and reasoned action (TRA). The sampling technique used is non-probability sampling with a total sample of 60 respondents with the characteristics of having accessed the Bukalapak online shopping site, having seen Bukalapak advertisements on television, and with ages ranging from 19-34 years. Analysis of the data used is a simple linear regression test. The results of the study indicate that there is a significant influence of exposure to television advertising and website quality on purchasing decisions on Bukalapak online shopping sites.